Risk of dissection in thoracic aneurysms associated with mutations of smooth muscle alpha-actin 2 (ACTA2). Issue 4 (6th January 2011) - Disabella, Eliana; Grasso, Maurizia; Gambarin, Fabiana Isabella; Narula, Nupoor; Dore, Roberto; Favalli, Valentina; Serio, Alessandra; Antoniazzi, Elena; Mosconi, Mario; Pasotti, Michele; Odero, Attilio; Arbustini, Eloisa
Abstract : Objective: To evaluate the prevalence and phenotype of smooth muscle alpha-actin ( ACTA2 ) mutations in non-syndromic thoracic aortic aneurysms and dissections (TAAD). Design: Observational study of ACTA2 mutations in TAAD. Setting: Centre for Inherited Cardiovascular Diseases. Patients: A consecutive series of 100 patients with TAAD. Exclusion criteria included genetically confirmed Marfan syndrome, Loeys–Dietz type 2, familial bicuspid aortic valve and Ehlers–Danlos type IV syndromes. Interventions: Multidisciplinary clinical and imaging evaluation, genetic counselling and testing of ACTA2, and family screening. Main outcome measures: Prevalence of ACTA2 mutations and corresponding phenotypes. Results: TAAD was familial in 43 cases and sporadic in 57 cases. Five mutations in the familial TAAD group (12%) were identified that were absent in controls. The known p.Arg149Cys and the novel p.Asp82Glu, p.Glu243Lys and p.Val45Leu mutations affected evolutionarily conserved residues. The IVS4+1G>A mutation was novel. Of 14 affected relatives, 13 were carriers of the mutation identified in the corresponding proband while one deceased relative had no genetic test. Type A dissection was the first manifestation of aortic aneurysm in four probands and occurred unexpectedly in five relatives. The aortic aneurysm was age dependent and absent in mutated children. Of nine patients who had acute dissection, five died following surgery. At dissection, the size of the aortic aneurysm ranged from 40 mm to 95 mm. Extravascular, ocular, skeletal, nervous and pulmonary traits were variably associated with TAAD, with iris flocculi being most common. Conclusions: Timely diagnosis of TAAD in the probands, genetic counselling and family screening identify predisposed relatives and prevent catastrophic aortic dissections.